Penerapan Buku Saku Digital Sebagai Media Edukasi Gizi Untuk Ibu Hamil Di Era Digital - Mirna, Mirna; Prianti, Ani T; Ohorella, Fadjriah (Madu : Jurnal Kesehatan, 2024)
Improving the nutritional knowledge of pregnant women is a vital effort to support the health of both mothers and their babies. This study aims to evaluate the use of a digital pocketbook as a nutritional education tool for pregnant women. A quasi-experimental study with a pretest-posttest control group design involved 50 pregnant women divided into two groups: intervention (digital pocketbook) and control (conventional methods), each consisting of 25 participants. Data were collected using questionnaires administered before and after the intervention. The results showed a significant increase in knowledge in both groups, with the mean knowledge score in the intervention group increasing from 58.2 to 85.4 (p < 0.05), compared to the control group, which increased from 59.1 to 71.5 (p < 0.05). This study concludes that digital pocketbooks are an effective nutritional education tool for improving pregnant women’s knowledge in the digital era, as they enable flexible, interactive, and repeatable learning. It is recommended that the content of digital pocketbooks be regularly updated to remain relevant to the needs of pregnant women and advancements in nutritional and health sciences.